Facsimile : Uitgave 38-39. - Stichting De Zaak, Groningen; Kleerebezem, Jouke; Scholten, Hans (Groningen : Stichting de Zaak, 1988)
Blake, John ; Caramelle, Ernst ; Graham, Rodney ; van Grunsven, Jan ; van der Heyden, J.C.J. ; Nypels, Rob ; Oorebeek, Willem ; Pitz, Hermann ; Puckey, Tom ; Rombouts, Guy ; Zaugg, Rémy ; de Zeeuw, Mirjam
2 volumes : Facsimile, Stichting De Zaak, Groningen, 23 oktober 1988 - 16 januari 1989
Nederlands
boek